Effect of Tillage and Sowing Methods on Wheat Production in the Upper Terraces of the Northern State (Sudan) - Dahab, Mohamed H.; Mahgoub, Mohamed A. (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to select the best tillage and sowing methods for large scale production of wheat in the Northern State of Sudan. Eight treatments comprising five tillage methods (Disc ploughing + disc harrowing + leveling; moldboard ploughing + disc harrowing + leveling; chisel ploughing + disc harrowing + leveling; light offset disc harrowing + leveling; zero tillage as control) and three sowing methods (manual broadcasting + cultivation; manual broadcasting + light disc harrowing; seed drilling on flat land) were compared in a split-plot design arrangement for two seasons (2000/ 01 and 2001/ 02). The greatest average yields were obtained by using disc plough + disc harrow + leveling (4.0 ton/ha) and chisel plough + disc harrowing + leveling (3.9 ton/ha) compared with other tillage methods. Seed drilling as well as cultivation after broadcasting resulted in significantly (P<0.01) higher average yields (3.9 ton/ha) than harrowing after broadcasting for the two seasons